2018
DOI: 10.1159/000486324
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling Pathophysiology of Crystalline Nephropathy in Ceftriaxone-Associated Acute Kidney Injury: A Cellular Proteomic Approach

Abstract: Background: Previous studies showed that ceftriaxone can cause acute kidney injury (AKI) in the pediatric population. This study proposed a cellular model of crystalline nephropathy in ceftriaxone-associated AKI and explored the related pathophysiology by using a proteomic approach. Methods: Ceftriaxone was crystallized with calcium in artificial urine. Madin-Darby Canine Kidney (MDCK) cells, a model of distal renal tubular cell, were cultured in the absence (untreated control) or presence of ceftriaxone cryst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…The dysproteinemia-related CN includes light chain cast nephropathy, also known as myeloma cast nephropathy, which is the most common dysproteinemia-related renal disease [53,54]. Crystalline nephropathy may develop during the use of drugs (ceftriaxone [55]), sulfadiazine [56], acyclovir [57], triamterene [58], atanazavir [59], and others that are excreted by the kidney (see details in recent review [60]). Calcium crystals CN is characterized by abundant tubular and interstitial deposits of calcium phosphate or CaOx crystals, easily distinguished by their tinctorial properties.…”
Section: Determinants Of Randall's Plaque Formationmentioning
confidence: 99%
“…The dysproteinemia-related CN includes light chain cast nephropathy, also known as myeloma cast nephropathy, which is the most common dysproteinemia-related renal disease [53,54]. Crystalline nephropathy may develop during the use of drugs (ceftriaxone [55]), sulfadiazine [56], acyclovir [57], triamterene [58], atanazavir [59], and others that are excreted by the kidney (see details in recent review [60]). Calcium crystals CN is characterized by abundant tubular and interstitial deposits of calcium phosphate or CaOx crystals, easily distinguished by their tinctorial properties.…”
Section: Determinants Of Randall's Plaque Formationmentioning
confidence: 99%
“…Chatchen et al . [ 10 ] studied the underlying pathophysiology of ceftriaxone-associated acute kidney injury via cellular proteomic in vitro cell model approach, whereby cell survival and adaptation were mediated by the concurrent upregulation of Hsp70, whereas downregulation of annexin A1 was proposed as the negative-feedback mechanism to mitigate the stressful effects of ceftriaxone crystallization, cell growth arrest and delayed wound healing of distal tubular cells after ceftriaxone crystal exposure, shedding light on collateral damage in combination therapy involving ceftriaxone and other stressors. Kimata et al .…”
Section: Discussionmentioning
confidence: 99%
“…Ceftriaxone is a third-generation cephalosporin and is characterized by its broad spectrum, high safety profile and long plasma half-life, rendering it among the commonly used antibacterial drugs during the childhood period for the treatment of different bacterial infections [24]. Ceftriaxone has been known for its biliary side effects, including biliary sludge and pseudolithiasis since the late 1980s [25].…”
Section: Ceftriaxonementioning
confidence: 99%
“…This may be the underlying mechanism for its biliary side effects [29]; however, the mechanism of ceftriaxone-induced nephrolithiasis is not yet completely understood [31]. In this setting, several authors have tried to investigate the pathophysiological mechanism for ceftriaxone-associated renal side effects [24,46]. Zhang et al [46] demonstrated in their animal study that the rats that were administered ceftriaxone and calcium showed a significantly lower volume of 24-h urine, with a significant increase in serum creatinine and blood urea nitrogen levels, suggesting that calcium chloride is important for stone formation.…”
Section: Pathophysiologymentioning
confidence: 99%
See 1 more Smart Citation